Gas Leakage From Shallow Ponding Magma and Trapdoor Faulting at Sierra Negra Volcano (Isabela Island, Galápagos). (18th February 2022) - Aiuppa, Alessandro; Allard, Patrick; Bernard, Benjamin; Lo Forte, Francesco Maria; Moretti, Roberto; Hidalgo, Silvana
Abstract: We report on new volcanic gas composition results acquired in October 2017 at Minas de Azufre, a persistent fumarolic field topping the resurgent Sierra Negra caldera, in the Galápagos archipelago. Our results indicate that the Minas de Azufre fumaroles are moderately hydrous (52–64 mol.% H2 O) and rich in CO2 (35–46 mol.%), with total sulfur ( S T ) being 21–35 times less abundant than CO2 . SO2, the most abundant S species, is released at an average rate of 19 ± 9 tons/day. Using a volatile saturation model that provides the composition of magmatic gases at equilibrium with western Galápagos basaltic melt (48 wt. % SiO2 ) in the 400–0.1 MPa pressure range, we infer that Minas de Azufre fumarolic emissions consist of a mixture of (a) magma‐derived gases coexisting with a melt at ∼50–60 MPa and (b) shallow meteoric water. We thus propose that the fumaroles are supplied by outgassing of magma stored in a ∼2 km deep sill‐like reservoir underneath the caldera floor, and that the trapdoor fault system at the western margin of the resurgent caldera block acts as a preferential pathway for magmatic gas ascent and surface discharge. Our results thus suggest that, in contrast to the majority of the volcano‐hosted hydrothermal systems worldwide, Minas de Azufre releases a relatively pristine magmatic gas. Plain Language Summary: Magmatic gas released by intraplate, hot‐spot related volcanism can offer insight into the abundance and distribution of volatiles in the Earth's upper mantle. Unfortunately however, the available data set for hot spot magmatic gases is sparse and incomplete, due to relatively infrequent eruptions and the remote location of many hot‐spot volcanoes. Here, we present novel information for the gas chemistry and emission rate at the Minas de Azufre fumarolic field, the most active persistent gas manifestation on Sierra Negra volcano, in the western part of the Galápagos hotspot. We interpret our gas observations in tandem with results of a volatile saturation model that calculates the equilibrium composition of magmatic gases coexisting with basaltic melt under P‐T conditions relevant to Galápagos volcanism. From this comparison, we conclude that the Minas de Azufre fumarolic emissions are fed by degassing of basaltic magma stored in a ∼2 km deep sill underneath the Sierra Negra caldera floor, and that the trapdoor fault system at the western margin of the resurgent caldera block acts as a preferential pathway for magmatic gas leakage and surface discharge. Our results are relevant to a better understanding of Sierra Negra volcano and contribute to extending the volcanic gas catalog for hot‐spot volcanism. Key Points: The composition and mass flux of volcanic gases from Minas de Azufre, in the Sierra Negra Caldera (Galápagos), are determined Fluids are interpreted as prevalently derived from a shallow (∼2 km deep) magmatic sill underneath the caldera floor Trapdoor faults at the resurgent caldera block's margin favor magmatic gas leakage and surface discharge